Morphological and temporal variation in early embryogenesis contributes to species divergence in Malawi cichlid fishes. Issue 2 (7th February 2023) - Marconi, Aleksandra; Yang, Cassandra Zie; McKay, Samuel; Santos, M. Emília
Abstract: The cichlid fishes comprise the largest extant vertebrate family and are the quintessential example of rapid "explosive" adaptive radiations and phenotypic diversification. Despite low genetic divergence, East African cichlids harbor a spectacular intra‐ and interspecific morphological diversity, including the hyper‐variable, neural crest (NC)‐derived traits such as coloration and craniofacial skeleton. Although the genetic and developmental basis of these phenotypes has been investigated, understanding of when, and specifically how early, in ontogeny species‐specific differences emerge, remains limited. Since adult traits often originate during embryonic development, the processes of embryogenesis could serve as a potential source of species‐specific variation. Consequently, we designed a staging system by which we compare the features of embryogenesis between three Malawi cichlid species— Astatotilapia calliptera, Tropheops sp. 'mauve' and Rhamphochromis sp. "chilingali"—representing a wide spectrum of variation in pigmentation and craniofacial morphologies. Our results showed fundamental differences in multiple aspects of embryogenesis that could underlie interspecific divergence in adult adaptive traits. First, we identified variation in the somite number and signatures of temporal variation, or heterochrony, in the rates of somite formation. The heterochrony was also evident within and between species throughout ontogeny, up to the juvenile stages. Finally, the identified interspecific differences in the development of pigmentation and craniofacial cartilages, present at the earliest stages of their overt formation, provide compelling evidence that the species‐specific trajectories begin divergence during early embryogenesis, potentially during somitogenesis and NC development. Altogether, our results expand our understanding of fundamental cichlid biology and provide new insights into the developmental origins of vertebrate morphological diversity. Abstract : Lake Malawi cichlids harbor a spectacular intra‐ and interspecific morphological diversity yet understanding of how early in ontogeny species‐specific phenotypes emerge remains limited. A comparative analysis of early development of three divergent Malawi cichlids reveals anatomical and timing differences during embryogenesis and indicates divergence of adult morphological traits before their overt formation. Research highlights: This work details the early development of three divergent Lake Malawi cichlids. A comparative analysis reveals anatomical and timing differences during embryogenesis and indicates divergence of species' morphologies before their overt formation.